The Convention for protection and sustainable development of Carpathian Mountains - Kozłowski, Stefan (Studia Ecologiae et Bioethicae, 2004)
The article comprehends the description of coming into being The Convention for the protection and sustainable development of the Carpathian Mountains. It leads the analysis of the essence of this Convention and shows its importance for this part of Europe and for Poland. The article points also at the perspective and the possibility of putting into the execution of Convention resolutions.